Mestre de Sabará: metodologia para análise formal e estudo atributivo - Flavia Costa Reis (2022)
In the study of artistic works, it is known that there are several methods of analysis that can contribute to a better understanding of the production of a particular artist, arriving at new attributions, according to the styles found. Aiming to deepen the methodology of formal analysis of devotional sculptures, we used the “Morelian” method as a basis for the research, and developed flowcharts for each stage to guide, in a didactic way, the study of the anatomical details of the works. The research was based on the works of Mestre de Sabará, an artist from Minas Gerais identified during the elaboration of the National Inventory of Movable and Integrated Goods by the former SPHAN, in 1986 and 1987. The clipping took place around the works found in Sabará, mainly in the Church of São Francisco, with a total of 30 sculptures being analyzed. The analysis process was carried out through a comparative study of the most significant formal anatomical elements of the works, identifying similarities and defining the main styles. As a result we are confirming, refuting or establishing new assignments to the master and his workshop. With this work, we wish to contribute to the greater visibility, appreciation and preservation of the precious collection of Mestre de Sabará.